2009
DOI: 10.1002/ijc.24157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cantharidins on leukemic stem cells

Abstract: To identify an agent with specific activity against leukemic stem cells (LSCs), we evaluated compounds that targeted hepatic leukemia factor (HLF), a gene implicated in hematopoietic stem cell (HSCs) regulation, that we found overexpressed in LSCs. Cantharidin, a natural toxin from blister beetles, used as medicinal agent since antiquity, has been described to modulate the HLF competitor NFIL3 and is under clinical evaluation as an antitumor and antimetastatic agent. The molecule is not a substrate for multidr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 72 publications
0
62
0
Order By: Relevance
“…Cantharidin has been shown to be active in cervical, tongue, gingival, mucoepidermoid carcinoma, adenocystic carcinoma, neuroblastoma, bone, ovarian, and colon cancer cell lines among others (Wu et al 1992;McCluskey et al 2000;Sakoff et al 2002). Effect of cantharidins against hepatocellular and colorectal tumors (Wang et al 2000;To et al 2005;Chen et al 2005) and leukemic stem cells (Dorn et al 2009) has been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Cantharidin has been shown to be active in cervical, tongue, gingival, mucoepidermoid carcinoma, adenocystic carcinoma, neuroblastoma, bone, ovarian, and colon cancer cell lines among others (Wu et al 1992;McCluskey et al 2000;Sakoff et al 2002). Effect of cantharidins against hepatocellular and colorectal tumors (Wang et al 2000;To et al 2005;Chen et al 2005) and leukemic stem cells (Dorn et al 2009) has been well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Cantharidin has anti-cancer activity inhibiting human leukemia cell lines growth in vitro (Rauh et al 2007). Unlike other chemotherapeutic agents, cantharidin acts on leukemia progenitor and stem cells (Dorn et al 2009). Derivatives of cantharidin also inhibit the growth of prostate, colon, oral, cervical, and gall bladder cancer cell lines (Hill et al 2007;Liu and Chen 2009).…”
Section: Beetles (Cantharidin)mentioning
confidence: 99%
“…and Mylabris cichorii Linn. ), is used as a traditional Chinese medicine with anticancer, antibiotic, antiviral, and immune-regulating activities [6,7]. Recent studies have shown that cantharidin and its derivatives exert cytotoxic effects against cancer cells.…”
Section: Introductionmentioning
confidence: 99%